1982
DOI: 10.1093/infdis/146.6.719
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Microbiologic Study of Bacteriuria in Patients with Chronic Indwelling Urethral Catheters

Abstract: Bacteriuria is common in chronically catheterized patients and is associated with both acute and chronic complications. Of 605 consecutive weekly urine specimens from 20 chronically catheterized patients, 98% contained bacteria at high concentrations and 77% were polymicrobial. The mean interval between new episodes of bacteriuria was 1.8 weeks. Most species of bacteria caused five to seven new episodes of bacteriuria per 100 weeks of catheterization. Even though access to the catheter lumen was similar, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
384
3
11

Year Published

1984
1984
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(408 citation statements)
references
References 10 publications
10
384
3
11
Order By: Relevance
“…As mentioned earlier, Morrison and Wenzel (6) found a similar increase in UTIs caused by enterococci. Risk factors for enterococcal UTI have been identified as urinary tract instrumentation or catheterization (6,7,71,72), other genitourinary tract pathology (6,7), and previous use of antibiotics especially cephalosporin (6). One study noted previously showed that an increase in enterococcal UTI paralleled an increase in cephalosporin use in the hospital (6).…”
Section: Epidemiologic Aspects Of Enterococcal Infectionmentioning
confidence: 99%
“…As mentioned earlier, Morrison and Wenzel (6) found a similar increase in UTIs caused by enterococci. Risk factors for enterococcal UTI have been identified as urinary tract instrumentation or catheterization (6,7,71,72), other genitourinary tract pathology (6,7), and previous use of antibiotics especially cephalosporin (6). One study noted previously showed that an increase in enterococcal UTI paralleled an increase in cephalosporin use in the hospital (6).…”
Section: Epidemiologic Aspects Of Enterococcal Infectionmentioning
confidence: 99%
“…24 A study of 20 patients who were chronically catheterized found that 98% of 605 consecutive weekly urine specimens contained >10 5 bacteria/mL of urine, and 77% of the urine specimens contained multiple species. 25 Monthly urine cultures for patients with long-term indwelling catheters show that the bacterial flora is constantly shifting and changing, regardless of antibiotic use. 26 …”
mentioning
confidence: 99%
“…8 Furthermore, the relationship between Proteus bacteriuria and urinary catheter encrustation and blockage is well documented. 9,10 Proteus bacteriuria has likewise been documented in persons with SCI, 1,11,12 but not specifically in association with stones.…”
Section: Resultsmentioning
confidence: 99%